Effect of normalizing and tempering temperatures on microstructure and mechanical properties of P92 steel. (August 2015) - Barbadikar, Dipika R.; Deshmukh, G.S.; Maddi, L.; Laha, K.; Parameswaran, P.; Ballal, A.R.; Peshwe, D.R.; Paretkar, R.K.; Nandagopal, M.; Mathew, M.D.
Abstract: In the present investigation, systematic studies on microstructure and mechanical properties of P92 steel subjected to various normalizing (1313–1353 K) and tempering (1013–1053 K) temperatures were carried out. The effect of heat treatment on microstructural parameters revealed an increase in grain size, lath width and decrease in the area fraction of the precipitates with an increase in normalizing temperature. The precipitate size has not changed significantly with increase in the normalizing temperature; rather it increased with increase in tempering temperature. Activation energy calculations confirmed the two fold mechanisms that dominate the tempering behavior. As a consequence, yield stress (YS) and ultimate tensile strength (UTS) were found to change with normalizing and tempering temperatures. P92 steel normalized at 1353 K and tempered at 1013 K was found to have the best combination of strength and ductility. Highlights: P92 steel subjected to normalizing (1313–1353 K) and tempering (1013–1053 K) temperatures. YS, UTS and hardness increased with normalizing and decreased with tempering temperatures. Precipitate size, lath width increased with increase in tempering temperature. Ductility increased with normalizing and tempering temperatures with a plateau at 1033 K. Activation energy calculations confirmed two fold mechanism for tempering behavior. Normalizing at 1353 K and tempering at 1013 K, optimum combination for ASME P92 steel.